2019
DOI: 10.1097/rlu.0000000000002391
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Venous Infarct Mimicking Cerebral Metastasis in 18F-FDG PET/CT

Abstract: A 68-year-old woman with colon carcinoma was referred to 18F-FDG PET/CT imaging for staging. In addition to primary tumor involvement, PET/CT demonstrated focal FDG uptake in the right temporal lobe suggestive of primary brain tumor or metastasis. To delineate the lesion, a brain MRI scan showed sigmoid sinus thrombosis and vasogenic edema in the right temporal lobe. The patient presented a history of right-sided headache that began 1 week before the PET/CT. Neurological examination and MRI findings were concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Other explanations include elevated cerebral blood volume, as well as activation of glucose transporters and increased glycolysis as a compensatory mechanism. [3][4][5][6][7][8][9][10] On the other hand, pattern of FDG accumulation in subarachnoid space in acute phase of SAH could be simply due to intracranial extravasation of FDG through the ruptured aneurysm. 11,12 This case demonstrated the different mechanisms of cerebral FDG accumulation in different types of intracranial hemorrhage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other explanations include elevated cerebral blood volume, as well as activation of glucose transporters and increased glycolysis as a compensatory mechanism. [3][4][5][6][7][8][9][10] On the other hand, pattern of FDG accumulation in subarachnoid space in acute phase of SAH could be simply due to intracranial extravasation of FDG through the ruptured aneurysm. 11,12 This case demonstrated the different mechanisms of cerebral FDG accumulation in different types of intracranial hemorrhage.…”
mentioning
confidence: 99%
“…Lin et al 2 suggested that the abnormal perihematomal glucose metabolism can be related to formation of vasogenic edema, and it may impair capillary integrity and increase blood-brain barrier permeability. Other explanations include elevated cerebral blood volume, as well as activation of glucose transporters and increased glycolysis as a compensatory mechanism [3][4][5][6][7][8][9][10]. On the other hand, pattern of FDG accumulation in subarachnoid space in acute phase of SAH could be simply due to intracranial extravasation of FDG through the ruptured aneurysm 11,12.…”
mentioning
confidence: 99%
“…[8][9][10] In this case, the increased FDG uptake beneath the subdural hematoma may be caused by increase in cerebral blood volume, activation of glucose transporters, and elevated glycolytic activity as a compensatory mechanism. 5,6,[11][12][13][14] More work is needed to explain the mechanism behind this phenomenon. Familiarity with the changes in cerebral glucose metabolism on PET after subdural hematoma may be helpful for optimal patient care.…”
mentioning
confidence: 99%
“…Acute subdural hematoma can cause elevated intracranial pressure leading to arterial compression, reduced cerebral perfusion pressure and impaired cerebral blood flow 8–10 . In this case, the increased FDG uptake beneath the subdural hematoma may be caused by increase in cerebral blood volume, activation of glucose transporters, and elevated glycolytic activity as a compensatory mechanism 5,6,11–14 . More work is needed to explain the mechanism behind this phenomenon.…”
mentioning
confidence: 99%
“…[ 4 ] This case highlights the importance of distinguishing true ischemic stroke that may exhibit metabolic activity in subacute phase from malignant brain tumors, such as gliomas, meningiomas, metastases, and uncommon lesions such as intravascular lymphoma, that can masquerade as acute stroke. [ 5 6 7 ] The above metabolic pattern of hypometabolic ischemic core and the surrounding hypermetabolic active inflammatory phase of subacute ischemic stroke representing viable tissues in the ischemic penumbra is attributable to the upregulation of parenchymal and microvascular glucose transporters (GLUTs), lateralization of GLUT1 mRNA expression to the ischemic hemisphere,[ 8 ] and “trapping” of 18 F-FDG-6-phosphate due to increased hexokinase activity in the peri-ischemic regions in response to hypoxia. The discrimination between brain tumors mimicking stroke and a true ischemic stroke is, therefore, crucial for proper management.…”
mentioning
confidence: 99%